Neutrophil-to-lymphocyte ratio as a predictor of poor outcomes of Mycoplasma pneumoniae pneumonia - Li, Dan; Gu, Haiyan; Chen, Lei; Wu, Ruxi; Jiang, Yazhou; Huang, Xia; Zhao, Deyu; Liu, Feng (Frontiers in Immunology, 2023)
Mycoplasma pneumoniae pneumonia (MPP) may lead to various significant outcomes, such as necrotizing pneumonia(NP) and refractory MPP (RMPP). We investigated the potential of the peripheral blood neutrophil-to-lymphocyte ratio (NLR) to predict outcomes in patients with MPP.This was a prospective study of patients with MPP who were admitted to our hospital from 2019 to 2021. Demographic and clinical data were collected from patient records and associated with the development of NP and RMPP and other outcome measures.Of the 1,401 patients with MPP included in the study, 30 (2.1%) developed NP. The NLR was an independent predictor of NP (odds ratio 1.153, 95% confidence interval 1.022-1.300, P=0.021). The probability of NP was greater in patients with a high NLR (≥1.9) than in those with a low NLR (<1.9) (P<0.001). The NLR was also an independent predictor of RMPP (odds ratio 1.246, 95% confidence interval 1.102-1.408, P<0.005). Patients with a high NLR were more likely to develop NP and RMPP and require intensive care, and had longer total fever duration, longer hospital stays, and higher hospitalization expenses than those with a low NLR (all P<0.005). This is a provisional file, not the final typeset article Discussion: The NLR can serve as a predictor of poor prognosis in patients with MPP. It can predict the occurrence of NP, RMPP, and other poor outcomes. The use of this indicator would allow the simple and rapid prediction of prognosis in the early stages of MPP, enabling the implementation of appropriate treatment strategies.